(3JQHjI GdeDefjf HGdJhbja Ydi MOhO HGWf Yde GdOjf hJGhjd OYGFe GdGSdGe aj GdMdGd hGdMQGes - (3GdbGVj GdfYeGf Hf Mjhf , CHh Mfjag GdfYeGf Hf eMeO Hf efUhQ Hf CMeO Hf Mjhf GdeUQj,J (B363 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eNQL GdhQb hebOQ GdQRb hHYO SeYJe CjgG GdeDefhf ajeG JbO cja Jfbdhf MGdkG HYO MGd ai MOhO GdOjf s
(3BNQgG (B:s
(3MJi jCPf dg ai Pdc Cgdg aGfge hGjgG GdeDefhf eG JYHOJe Hg XGgQ Ojfce hHGWfg s
(3HgG fXGe GdJYbjHIs
(3QJH Ydi (B12 (3LRAs
(3hcd LRA (B10 (3eLGdSs
(3GdehLhO eLdOjf s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3eJaQbGJs